Geographical patterns of mesothelioma incidence and asbestos exposure in Lombardy, Italy - Mensi, Carolina; De Matteis, Sara; Catelan, Dolores; Dallari, Barbara; Riboldi, Luciano; Pesatori, Angela Cecilia; Consonni, Dario (La Medicina del Lavoro, 2016)
Background: Measuring malignant mesothelioma (MM) occurrence is a useful means to monitor the impact of past asbestos exposure and possibly identify new sources of asbestos exposure. Objectives: Aim of this study is to describe the results of the MM registry of the Lombardy Region, North-West Italy, the most populated (currently, 10 million inhabitants) and industrialised Italian region. Methods: We extracted from the Lombardy Region Mesothelioma Registry (Registro Mesoteliomi Lombardia, RML) database all incident cases of MM (pleura, peritoneum, pericardium, and tunica vaginalis testis) with first diagnosis in 2000 through 2012. For each Province, we calculated crude and standardised incidence rates using Italy 2001, European, and world (Segi’s) standard populations. To examine spatial patterns of MM occurrence across municipalities we drew maps of crude rates smoothed according to the Besag, York and Mollié (BYM) method. Results: We recorded 4442 MM cases (2850 in men and 1592 in women), representing about one fourth of MM cases occurring in Italy. Occupational exposure was more frequent in men (73.6%) than in women (38.2%). The crude regional rates were 4.7 per 100,000 person-years in men and 2.5 per 100,000 person-years in women. The highest rates were observed in the Pavia Province (crude rates: 8.7 per 100,000 in men and 5.3 and per 100,000 person-years in women). Conclusions: This study documented high MM occurrence in both genders, attributable to extensive asbestos exposure in the past.